Contractualist reasoning, HIV cure clinical trials, and the moral (ir)relevance of the risk/benefit ratio. Issue 2 (2nd September 2016) - Kumar, Rahul
Abstract : Institutional review boards (IRB) normally require of a morally defensible clinical trial that any trial participant will benefit from the inquiry, or at least not be exposed to a significant risk of having their prospects worsened by participating. Stage 1 HIV cure trials tend not to meet this requirement. Does that show them to be morally indefensible? Utilitarian thinking about this question supports a negative answer. But one might reasonably expect a Kantian moral theory to support the conclusion that exposing trial participants to a significant risk of their prospects being worsened by their participation to be morally indefensible, on grounds that this would be a clear case of using a person as a mere means. In this paper, I argue, drawing on Kantian contractualist thinking, that requiring the risk/benefit ratio for participants be positive if a trial is to be morally defensible does not in fact gain any support from Kantian thinking about morality.